Structure of the heterogeneous L-S junction region of human cytomegalovirus strain AD169 DNA. - Tamashiro, J C (1984)
The genome of human cytomegalovirus strain AD169 contains a region of heterogeneity located at the junction between the long (L) and short (S) components of the viral DNA. Twelve cloned L-S junction fragments were studied by using the restriction enzymes HaeII and XhoI. The region of heterogeneity was localized within a single HaeII restriction fragment. The enzyme XhoI was used to subdivide this region and revealed the presence of three types of heterogeneity within the junction fragments. Each of the cloned junction fragments contained one of the following fragments: 0.553, 0.95, or 1.35 kilobase pairs (referred to as class I heterogeneity). Class II heterogeneity was defined as the presence of tandem duplications of class I fragments. In addition, a variable number (0 to 5) of a 0.2-kbp fragment (class III heterogeneity) was observed. Mapping of these fragments with partial XhoI digestions revealed that the class I and class III heterogeneous fragments were adjacent. The DNA sequence of the smallest cloned L-S junction fragment was determined and analyzed. This junction fragment contained a single 0.553-kbp XhoI fragment and no copies of the 0.2-kbp fragment. The 0.553-kbp XhoI fragment was similar in structure to the a-sequences of herpes simplex virus types 1 and 2. In addition, a region of homology was found between the a sequences of herpes simplex virus types 1 and 2 and the 0.553-kbp XhoI fragment from the human cytomegalovirus junction.